2003
DOI: 10.1182/blood-2002-10-3252
|View full text |Cite
|
Sign up to set email alerts
|

Late relapses evolve from slow-responding subclones in t(12;21)-positive acute lymphoblastic leukemia: evidence for the persistence of a preleukemic clone

Abstract: TEL/AML1-positive childhood acute lymphoblastic leukemias (ALLs) generally have low-risk features, but still about 20% of patients relapse. Our initial molecular genetic analyses in 2 off-treatment relapses suggested that the initial and relapse clones represent different subclones that evolved from a common TEL/ AML1-positive, treatment-resistant precursor. In order to further elaborate on this hypothesis, we studied 2 patients with late systemic relapses of their TEL/ AML1-positive ALL (41 months and 49 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
52
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 39 publications
8
52
0
Order By: Relevance
“…In the remaining case (UPN 15) and also in another four cases, we were able to evaluate and confirm that the clonotypic genomic TEL-AML1 fusion sequence, believed to mark the initiated preleukemic clone (8,17,28), was identical at relapse and diagnosis. A prediction of the hypothesis is that TEL deletions, as common but secondary events, should be different in their genomic boundaries at diagnosis and relapse.…”
Section: Discussionmentioning
confidence: 72%
“…In the remaining case (UPN 15) and also in another four cases, we were able to evaluate and confirm that the clonotypic genomic TEL-AML1 fusion sequence, believed to mark the initiated preleukemic clone (8,17,28), was identical at relapse and diagnosis. A prediction of the hypothesis is that TEL deletions, as common but secondary events, should be different in their genomic boundaries at diagnosis and relapse.…”
Section: Discussionmentioning
confidence: 72%
“…37,38 As an added bonus, this technology also provides relevant information about a variety of genetic lesions that characterize several other important TEL/AML1À leukemia subgroups such as those with TEL deletions, AML1 gene amplifications and high hyperdiploid karyotypes, which are hardly retrievable on a routine basis with any other procedure or not visible without adequate metaphase preparations. 21,22,32,40,41 The 25% incidence rate of TEL/AML1 þ cases in our study is in the upper range of the 18-26% reported in RT-PCR screening surveys.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 In two patients, the respective FISH patterns remained identical, which indicated a genuine reoccurrence of the original leukemic FISH analysis of secondary abnormalities in TEL/AML1 þ ALL A Attarbaschi et al clone. In six patients, on the other hand, the distribution of the secondary abnormalities was different in the diagnostic and relapse samples.…”
Section: Interphase Fish Of the Relapsed Tel/aml1 þ Patientsmentioning
confidence: 99%
“…Rapid and sustained disappearance of the dominant leukemia clones and a slow response of the smaller (preleukemic) clones upon first chemotherapy has been observed in t(12;21)-positive ALL patients. 33,34 Combination therapy may fail to eradicate the preleukemic clone, which may, after acquiring a new second leukemogenic hit, give rise to a new leukemia that is (falsely) being interpreted as a relapse of the original leukemia. 35 It is of interest to study whether the early relapses that occur amongst patients without additional genetic abnormalities in TEL or AML1, or with an extra copy of der(21)t(12;21), may be due to other secondary leukemogenic hits rather than the original leukemia.…”
Section: Discussionmentioning
confidence: 99%